Knowledge attitude and practice of contraception among antenatal care patients - Sangavi, Radha; Hatnoor, Shivappa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Strategies have been engaged by different governments in improving these indices amongst which is the use of family planning. Hence; authors planned the present study to assess the knowledge, attitude and practice of contraception among antenatal care patients. Methods: A total of 100 patients were enrolled in the present study. With the help of structured anonymous self-administered questionnaire, interviewing of the attendees of the antenatal clinic was done. The questionnaire was framed with aim of obtaining the clinical and demographic details of the subjects. All the data collecting interviews were conducted at the antenatal clinic. The participants were distributed a questionnaire and assistance given to any attendee with literal difficulty in filling the forms. The data obtained were collated in a purpose designed worksheet prepared for this study. Results: 78 percent of the subjects were aware about contraception, while the remaining 22 percent of the subjects were unaware about contraception. Knowledge of subjects about barrier method of contraceptive was present in 78 subjects. Conclusions: Antenatal women appear to have significant knowledge in relation to contraception.